ULTRASTRUCTURE AND ELEMENTAL ANALYSIS OF HYPOXIS HEMEROCALLIDEA: A MULTIPURPOSE MEDICINAL PLANT - Afolayan, Anthony J; Otunola, Gloria A (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Herbal medicine is a popular means of medical management in some parts of the world especially in Africa. Hypoxis hemerocallidea Fisch.C.A.Mey. & Avé-Lall, also known as African potato of the Hypoxidaecae family, is one of the medicinal plants that have enjoyed long usage as an herbal medicine in South Africa. In this study, the morphology and elemental constituents of H. hemerocallidea leaf was investigated to correlate the functional role of the ultrastructure in the production of therapeutic compounds. Materials and Methods: Fresh leaves of H. hemerocallidea were prepared for analysis using standard methods. The ultrastructure and crystal deposits of the plant were assessed using scanning electron microscopy (SEM), and energy dispersive x-ray (EDX). Results: It was observed that the leaves were characterised by multicelullar glandular and non glandular trichomes which are sparsely distributed over the entire surfaces. The glandular trichomes (GTs) in H. hemerocallidea leaf have boulbous heads which are probably filled with secretions, while the non glandular trichomes were long, fibrous and sparse. EDX-SEM of Hypoxis hemerocallidea leaf revealed that carbon, oxygen, nitrogen and silicon are the major components of the deposits, while other elements such as iron, sulphur, sodium, calcium, magnesium, potassium, manganese, iodine, chromium and iodine were present in small but variable amounts. Conclusion: The presence of these elements which are crucial to maintaining good health, in addition to other bioactive constituents might be accountable for the multipurpose therapeutic uses of Hypoxis hemerocallidea in the treatment of cancers, HIV/AIDS related diseases, urinary tract infections, cardiovascular disorders, diabetes and other chronic ailments of humans